2022
DOI: 10.3389/fonc.2022.933646
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic effects of nab-PTX and anti-PD-1 antibody combination against lung cancer by regulating the Pi3K/AKT pathway through the Serpinc1 gene

Abstract: Lung cancer is a type of cancer with higher morbidity and mortality. In spite of the impressive response rates of nab-paclitaxel (nab-PTX) or programmed cell death-1 (PD-1) and its ligand inhibitors, the effective treatment remains limited. Currently, alternative strategies aim at drug combination of nab-PTX and PD-1/PD-L1 inhibitors. Even as the clinical impact of the combined agents continues to increase, basic research studies are still limited and the mechanisms underlying this synergy are not well studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Nab-paclitaxel has been shown effective as a first-line treatment 28 and demonstrated longer progression-free survival than paclitaxel in first-line treatment for advanced gastric cancer 30 . Third, nab-paclitaxel has a synergistic effect with immunotherapy 61 , 62 . In addition, nab-paclitaxel has a synergistic effect with radiotherapy in lung cancer, pancreatic cancer, and head and neck squamous cancer, among others 43 , 63 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Nab-paclitaxel has been shown effective as a first-line treatment 28 and demonstrated longer progression-free survival than paclitaxel in first-line treatment for advanced gastric cancer 30 . Third, nab-paclitaxel has a synergistic effect with immunotherapy 61 , 62 . In addition, nab-paclitaxel has a synergistic effect with radiotherapy in lung cancer, pancreatic cancer, and head and neck squamous cancer, among others 43 , 63 65 .…”
Section: Discussionmentioning
confidence: 99%
“…In the PARAMOUNT study [39], patients who had maintenance Pemetrexed had an mOS of 13.9 months, and a later systematic review of the clinical trial population [40] showed that patients with EGFR mutations (without untreated brain metastases) who received Pemetrexed-containing regimens after TKI exhaustion had a weighted mOS of 15.91 months. Therefore, most novel chemo-immunotherapy studies chose to disregard the possible immunotherapy-potentiating effect of Paclitaxel [41][42][43] in favour of the possible cytotoxic advantage of Pemetrexed chemotherapy. IMpower151 [35] claimed to use the original ABCP regimen, but 97.4% of patients received Pemetrexed instead of Paclitaxel, although, in contraposition with the other studies, it included Bevacizumab in both arms and enrolled patients with EGFR and ALK genomic alterations (as well as patients without actionable mutations).…”
Section: Discussionmentioning
confidence: 99%
“…We further found that the synergistic mechanism of this regimen may lie in depleting Treg ratio to activate an immune response. However, due to the limitations of sample size, retrospective and single-center design of this study, many problems need to be resolved, such as the exact molecular mechanism ( 20 ), further optimization of the regimen, screening for the priority population, elucidating resistance mechanism ( 40 ), and so on. With the rapid development and accumulation of clinical experience of IO application, these puzzles will be gradually resolved and more and more patients will be able to benefit from this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, considering the higher penetrance capacity relative to docetaxel or paclitaxel, nabptx would probably be a more suitable partner for the combination of PD-1/PD-L1 inhibitors (11). Accumulating evidence has shown that the drug combination of nab-ptx and PD-1/PD-L1 inhibitors in solid tumors exerts obvious synergistic effect with lower toxicities (16)(17)(18)(19), although the mechanism remains unknown (20). With regard to PD-1/ PD-L1 inhibitors, in China, camrelizumab was the first PD-1/PD-L1 antibody to be approved by the National Medical Products Administration (NMPA) in 2019 for the first-line treatment of advanced NSCLC (21,22).…”
Section: Introductionmentioning
confidence: 99%